Optimization of cultivation conditions to enhance the expression of recombinant VDAC2 from gallus gallus - Ahmad Hassan, Nurhidayah; Amid, Azura; Mohd. Salleh, Hamzah (Journal of Pure and Applied Microbiology, 2014)
VDAC2 protein identified to be over expressed in over-stunned chicken is a potential biomarker in differentiating stunned chicken and the voltage applied during the process. The VDAC2 gene was amplified by proofread DNA polymerase, then purified and inserted into pENTR-TEV-D-TOPO entry vector and transformed into One Shot TOP 10 Chemically Competent E. coli. The entry clone then was sub cloned into pDEST17 expression vector using LR recombinasein E. coli DH5á as the host. The vector construct was transformed into E. coli BL21-AI for protein expression. Recombinant VDAC2 protein was purified by affinity chromatography using Ni-NTA spin-column. Western blot using polyclonal anti-N terminal human VDAC2 and anti-His tag, followed by secondary antibody AP goat anti-rabbit revealed a 34 kDa protein, confirming the expression of recombinant VDAC2. Post-induction temperature, concentration of L-arabinose and postinduction time were selected for optimization studies under Response Surface Methodology (RSM). The optimum predicted cultivation conditions for the maximum expression of recombinant VDAC2 was found to be at 29oC post-induction temperature, 6.8 hour post-induction time and 0.5% (w/v) L-arabinose with a predicted expression of recombinant VDAC2 intensity of 0.459. The experimental expression of recombinant VDAC2 intensity obtained was 0.496, which was very close to the predicted value. The expression of recombinant VDAC2 improved by almost 6-fold after the optimization process. Therefore, RSM is a suitable method for optimizing recombinant VDAC2 expression in E. coli to provide a better understanding of its characteristics and propertiesto become abiomarker in detecting over-stunned chicken.